Antibacterial activity and ion release of bonding agent containing amorphous calcium phosphate nanoparticles - Chen, Chen; Weir, Michael D.; Cheng, Lei; Lin, Nancy J.; Lin-Gibson, Sheng; Chow, Laurence C.; Zhou, Xuedong; Xu, Hockin H.K. (Dental materials, 2014)
Recurrent caries at the margins is a primary reason for restoration failure. The objectives of this study were to develop bonding agent with the double benefits of antibacterial and remineralizing capabilities, to investigate the effects of NACP filler level and solution pH on Ca and P ion release from adhesive, and to examine the antibacterial and dentin bond properties. Nanoparticles of amorphous calcium phosphate (NACP) and a quaternary ammonium monomer (dimethylaminododecyl methacrylate, DMADDM) were synthesized. Scotchbond Multi-Purpose (SBMP) primer and adhesive served as control. DMADDM was incorporated into primer and adhesive at 5% by mass. NACP was incorporated into adhesive at filler mass fractions of 10%, 20%, 30% and 40%. A dental plaque microcosm biofilm model was used to test the antibacterial bonding agents. Calcium (Ca) and phosphate (P) ion releases from the cured adhesive samples were measured vs. filler level and solution pH of 7, 5.5 and 4. Adding 5% DMADDM and 10–40% NACP into bonding agent, and water-aging for 28 days, did not affect dentin bond strength, compared to SBMP control at 1 day (p>0.1). Adding DMADDM into bonding agent substantially decreased the biofilm metabolic activity and lactic acid production. Total microorganisms, total streptococci, and mutans streptococci were greatly reduced for bonding agents containing DMADDM. Increasing NACP filler level from 10% to 40% in adhesive increased the Ca and P ion release by an order of magnitude. Decreasing solution pH from 7 to 4 increased the ion release from adhesive by 6–10 folds. Bonding agents containing antibacterial DMADDM and remineralizer NACP were formulated to have Ca and P ion release, which increased with NACP filler level from 10% to 40% in adhesive. NACP adhesive was “smart” and dramatically increased the ion release at cariogenic pH 4, when these ions would be most-needed to inhibit caries. Therefore, bonding agent containing DMADDM and NACP may be promising to inhibit biofilms and remineralize tooth lesions thereby increasing the restoration longevity.